KONSEP KURIKULUM PENDIDIKAN DALAM PERSPEKTIF ISLAMIC WORLDVIEW - Rusmayadi; Mochamad Naufal Fauzan; Dayat Indra Hidayat; Rizki Imanudin; Isop Syafe'i (Tadbir: Jurnal Manajemen Pendidikan Islam, 2026)
This study analyzes the concept of curriculum development from the perspective of the Islamic worldview as a response to the persistent dichotomy between religious and secular sciences within Islamic educational institutions. Employing a qualitative method through a systematic literature review of 89 primary and secondary sources, this research examines the philosophical foundations of curriculum ontology, epistemology, and axiology along with the operational principles and implementation framework of an Islamic worldview-based curriculum. The findings reveal that an ideal curriculum must be grounded in the principle of tawhid, integrating the dimensions of visible and unseen reality, multiple sources of knowledge (revelation, reason and empiricism) and axiological orientations toward ma’rifatullah and falah. Five key principles were formulated: tawhid, balance, flexibility, fitrah-based humanism and world hereafter orientation, each with specific implementation indicators. The study further proposes the Integrated Tawhidic Educational Model (ITEM), which synthesizes Islamic values across learning objectives, content, pedagogy, and evaluation. This research contributes theoretically by offering a comprehensive philosophical conceptual framework and practically by providing an operational model that Islamic educational institutions can adopt to develop integrative, holistic and contextually relevant curricula suited to contemporary challenges.